Descriptive Errors in Heidegger’s Theory of «Being at Hand» - Fernández Beites, Pilar (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This article critically discusses the thesis proposed by Heidegger in Being and Time, which states that «being in the eyes (Vorhandenheit)» is based ontologically in the «being at hand (Zuhandenheit)». We try to justify that the theory being proposed by the Heidegger´s «being at hand», far from being an improvement over Husserl, is rather an incorrect description of the life world, which ignores the primordial sensitive and evaluative level, and neglects basic data as well as the nature, values, work of art or the lived body
Keywords: tools; technique; theory; Gestell; Being in the Eyes